Modeling And Docking Studies Of 4-Aminobutyrate Aminotransferase For Huntington’s Disease - HARISH PAREEK; PRASOON THAKUR; DIVYA RAY (International Journal of Pharma and Bio Sciences, 2011)
Huntington’s disease (HD) is a neurodegenerative disease and 4-aminobutanoic acid (GABA) is an inhibitory neurotransmitter in mammalian nervous system which regulates muscle tone of the body. GABA acts at inhibitory synapses in the brain by binding to specific transmembrane receptors in the plasma membrane of both pre- and postsynaptic neuronal processes. γ-Aminobutyrate aminotransferase (GABA-AT) degrades the inhibitory neurotransmitter GABA. GABA-AT, a pyridoxal-dependent enzyme, is a target for antiepileptic and several other serious neuroactive drugs including drugs for Huntington’s disease. Hence, its selective inhibition raises concentrations of GABA in brain. Defects in GABA-T cause accumulation of beta-alanine and gamma aminobutyric acid in plasma and spinal fluid, as well as accumulation of homocarnosine in spinal fluid. Symptoms include hyperreflexia, hypotonia, lethargia, macrosomia, mental retardation, and siezures. Therefore, GABA-AT is the preferential choice for inhibition to increase the concentration of GABA in brain. Therefore, an attempt was made to obtain the suitable inhibitors of GABA-AT by de novo creation of structurally flattering lead molecules which were further validated by docking analysis with GABA-AT protein. The screening of these results revealed that ( 2 S)- 3 - [( 3aR, 4S, 6R, 7aS) - 6 - methyloctahydro- 1 H - inden - 4 - yl] -2-(propanoylamino)propanoic acid was found as the best fit over Lipinski’s rule of five and other ADME parameters.